THE CHANGING STRUCTURE OF THE TRIBE IN THE PROCESS OF URBANIZATION - Tan, Mehmet; Fırat, Muhammet (My University, 2022)
The study deals with the changes faced by the tribes in the urbanization process. The city stands out as a place where modern life manifests. The tribe, on the other hand, is known to be an organizational form in which traditionalism and the sense of community is dominant. While the urban individual has an individual vision of the world, the individual in the tribal culture adopts a more collectivist attitude. In this sense, when compared to tribal relations, urban relations are a more superficial and not intimate. Basically, the tribe and the city refer to very different structures. The city structure and texture are unique to itself and the forms of social relations it dresses itself are therefore different from rural forms. Tribal structures are also very different from urban practices thereby causes conflict and difficulties for the individual. At this point, some adaptation problems arise because the tribe members strive to maintain a collectivist relationship. In addition, while there is no authority other than law in the city, a tribal individual needs to obey the tribal leader. As seen, the cities do not conform to the lifestyles of the tribesmen, forcing them to change. But not limited to this alone, this paradox ultimately results in the heterogeneity of the cities, leading to question the current issue of traditional tribal organizations in modern cities. Thus, the last word is that despite the rural areas that tribal background remains strong, the urban tribe has changed with the urbanization process.
Keywords: Sosyoloji; Kentsel Çalışmalar